Analisis Rencana Pelaksanaan Pembelajaran Kelas X Mapel PJOK Ditinjau dari HOTS di SMK Se-Kecamatan Kebumen - Nahar Salamah; Hermawan Pamot Raharjo (Indonesian Journal for Physical Education and Sport, 2023)
This study aims to analyze how well the class X PJOK RPP is about learning based on Higher Order Thinking Skills in SMKs in Kebumen District. This research is quantitative descriptive. The method in this research is survey. The population in this study were all PE teachers in SMK throughout Kebumen District The data analysis technique of this research is descriptive analysis. The results of the analysis of the lesson plan analysis for Class X Mapel PE in Vocational Schools throughout the Kebumen District in terms of HOTS showed the "very good" category with a percentage of 30%, the "good" category with a percentage of 30%, the "enough" category with a percentage of 30%, the category " less” with a percentage of 0%, the category of “very poor” with a percentage of 10%. From the results of the study, it can be concluded that the PE teachers in Vocational Schools throughout the Kebumen District have prepared the RPP properly and in accordance with the HOTS. Suggestions that researchers can give for PE teachers whose RPP is still in the sufficient category, the teacher should use operational verbs C4, C5, and C6, in choosing the method the teacher should use Discovery/Inquiry Learning, Problem based Learning, Project